Pembelajaran PAI Anak Tunagrahita dalam Menumbuhkan Dimensi Religius dan Karakter Mandiri - Tika Anjariani (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
This study aims to describe PAI learning in mentally retarded children in growing religious dimensions and independent character, analyze the results achieved, and the problems. This research is a qualitative descriptive with a religious psychology approach. The research is located at SLB Yapenas Condongcatur Yogyakarta. Data collection using passive participatory observation, semi-structured interviews, and documentation. Test the validity of the data using triangulation of sources and techniques. Data analysis uses data reduction, data presentation, and drawing conclusions. The result of the study are PAI learning focuses on teaching morals, prayer, the Qur'an, and basic material. The result achieved in PAI learning related to religious dimensions and independent character vary depending on the child's understanding obility. Meanwhile, the problem is that PAI learning is still taught by their respective group teachers; a sense of laziness and lack of enthusiasm for students; and lack of parental support